Percutaneous Transvenous Mitral Commissurotomy: SGNHC Experience - Rajbhandari, Rajib; KC, Man Bahadur; Bhatt, Y; Regmi, Shyam; Sharma, Deewakar; Rajbhandari, Sujeeb; Kansakar, Subodh; Malla, Rabi; Limbu, YR; Koirala, Bhagawan; Shrestha, NK (Nepalese Heart Journal, 2004)
One hundred patients had PTMC from June 2003 to January 2004, Seventy four percent of them were female. Youngest was 10 years and oldest was 5 8 years, Mean age was 25 years. Under 21 years were 26%, Atrial fibrillation was present in 32%, Mean MVA increased from range 0.91 cm2 to 1.90 cm2 with range of 0.5 cm? preprocedure to 2.3 cm2 post-procedure, Left atrial mean pressure decreased from average 19 mm Hg to 6 mm Hg. Subjective improvement was reported in 99%. There was no mortality. Significant MR (>2 Grade) was noted in 3 patients (3%) post- procedure. None developed severe MR. Procedure failed in two patients. None had cardiac tamponade. None had to undergo emergency surgery. One had systemic embolisation during the procedure which recovered subsequently.